Opiate of Christ; or, John's Gospel and the Spectre of Class. Issue 3 (3rd September 2015) - Myles, Robert
Abstract : This article applies a Libertarian Marxist lens to the Gospel of John. In doing so, it highlights the agrarian-aristocratic class struggle that is refracted in the text and also seeks to problematize hierarchical and authoritarian ideologies. Its point of departure is the recent political interpretations of John championed by Tom Thatcher (2009) and Warren Carter (2008), but it diverges significantly from these readings by observing how the gospel's so-called "subversive" quality has often been overstated and/or simply taken for granted. By focusing on the problematic re-inscription of hierarchies of power, the reading advanced below argues that John's heightening of imperial ideology in Jesus is at best unsubversive and at worst normalizing of a fascist-like impulse for racial and authoritarian purity.